À propos de quelques outils de collecte de données : réflexions sur les pratiques numériques en archéologie - Christophe Tufféry; Vincent Delvigne; Paul Fernandes; Céline Bressy-Léandri (Humanités Numériques)
Since 2006, several Collective Research Projects (PCR) entitled “Réseau de lithothèques” – which have been grouped together as part of a Research Group (GDR) since 2019 – have been collecting large volumes of spatial data on sedimentary silicified rocks (SSR) in France. An exhaustive and harmonised inventory of rock libraries containing these materials is also in progress. Several digital devices have been used for producing, pooling, analysing, sharing and rendering these spatial data: computer-aided drawing, geographic information systems, database management systems, data sharing and publication platforms, mobile applications. During the implementation of these tools, methodological and epistemological questions arose. They concern the design and implementation of such devices for researchers from heterogeneous disciplinary horizons (archaeology, prehistory, geography, petrography, mineralogy, geochemistry, etc.); their practices are modified, to a variable extent, by the conditions and contexts in which these digital devices are implemented.